Sufficiency thinking Thailand's gift to an unsustainable world - Bergsteiner, Harald; Avery, Gayle 1947- (Crows Nest, New South Wales Allen & Unwin, 2016)
Our world is under pressure, with growing inequalities in wealth and access to food and clean water. We depend too heavily on polluting fuels and diminishing natural resources. Traditional cultural practices are being swamped by global screen culture. The Thai model of sufficiency thinking aims to transform the mindset of a whole population to achieve the seemingly impossible: enriching everyone's lives in a truly sustainable way. Innovative management practices developed by King Bhumibol Adulyadej of Thailand have been applied across Thailand in agriculture, business, education, government and community organisations over the past two or more decades. In this book, chapters written by eminent Thai scholars explain sufficiency thinking and review its implementation in different sectors including community development, business, agriculture, healthcare, schools and even in prisons. Is Thailand unique in having discovered the holy grail of a more responsible form of capitalism? No, it is not, but it is the first country whose government has adopted this kind of thinking as national policy.
Part I: Introduction -- Part II: The sufficiency economy philosophy -- Part III: At the local and community levels -- Part IV: At the national level -- Part V: Sufficiency thinking in business -- Part VI: Actioning the future -- About Thailand.
Includes bibliographical references (pages 271-286) and index.
Keywords: Sustainable development -- Thailand